O papel do sell side no bom desempenho da sociedade impulsionado pelo Earn-out e o impacto das cláusulas de governança impostas pelo buy side nas operações de M&A - Valle, Clara Guizilim Braga do (2023)
This is a study on the Earn-Out mechanism, a tool designed to align the interests of the seller (sell side) with those of the buyer (buy side). It is conditional on a period during which the seller is obligated to continue participating in the company and achieving certain targets. The mechanism can overcome certain difficulties in closing mergers and acquisitions deals by considering both objective valuation parameters and the buyer's subjective perception of the sale's impact on results generation. The discussion will cover the legal nature, economic and social function, and applicability in Brazilian law, based on Law 6.404/76, as well as possible incentive metrics and obligations falling to the seller. Furthermore, it analyzes how the use of the mechanism is linked to the company's performance as a result of the sell side's work and effort, as agreed upon during the negotiations of the definitive contracts of the operation. However, one cannot discuss contractual obligations without addressing objective good faith in drafting and later in execution, in line with the articles of the Civil Code. Moreover, the seller may be subject to governance rules imposed by the buyer that could prevent the sell side from performing certain functions and hinder the achievement of targets. The debate presented here will focus on how a seller can operate freely within the business to achieve their goals if the buyer holds the controlling share and the majority of votes. Even with the synergy between the parties and the intention of best efforts for the company's growth, this discussion often arises because the buy side, being the controlling shareholder, may interfere with the executive seller's management and hinder the fulfillment of agreed metrics. Therefore, the idea is to present an overview of this conditioned mechanism with the impact of the governance discussion imposed by the buyer